Políticas públicas em âmbito federal para a população LGBTQIA+: do projeto participativo ao autoritário: Federal public policies for the LGBTQIA+ population: from a participatory to an authoritarian project (Simbiótica. Revista Eletrônica, 2023)
This text addresses public policies for the LGBTQIA+ population in Brazil by analyzing some decisions and profiles of occupants of central positions in the federal bureaucracy from the beginning of the Worker’s Party (PT) government (2003) to the Bolsonaro government (2019-2023). The qualitative and documental research used scientific works and news published in the mainstream media as data sources to reconstruct this history. It is argued that the PT political project, even with limits, can be considered a participatory one, while the project that occupied the federal government from Michel Temer to the Bolsonaro government can be classified as authoritarian. The research shows how authoritarian and participatory political projects came into dispute, threatening the rights of the LGBTQIA+ population.